2020
DOI: 10.3390/ani10061058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nutritional Restriction on the Hair Follicles Development and Skin Transcriptome of Chinese Merino Sheep

Abstract: The high concentration of secondary branched wool follicles is a distinctive feature of the Merino sheep. At present, the molecular control of the development and branching of secondary wool follicles (SF) remains elusive. To reveal the potential genes associated with the development of hair follicles, we investigated the characteristics of prenatal and postnatal development of wool follicles, and the transcriptional expression profile in fetuses/lambs from dams under either maternal maintenance or sub-mainten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Notably, the first enriched KEGG pathway was ribosomes at both E13 and E25. Similar results were found in a study on the sheep hair follicle; however, Lv et al (2020) reported that the nutrition-driven hair follicle development is associated with the enriched ribosome pathway, which suggests that hair/feather follicle development can be affected by the ribosome pathway. During the embryonic period in birds, rapid morphogenesis, differentiation, and development of various organs require support from cell division, consisting of quick connection of gene expression programs, acceleration of the translation programs, and quick regulation of protein synthesis ( Guo, 2018 ).…”
Section: Discussionsupporting
confidence: 88%
“…Notably, the first enriched KEGG pathway was ribosomes at both E13 and E25. Similar results were found in a study on the sheep hair follicle; however, Lv et al (2020) reported that the nutrition-driven hair follicle development is associated with the enriched ribosome pathway, which suggests that hair/feather follicle development can be affected by the ribosome pathway. During the embryonic period in birds, rapid morphogenesis, differentiation, and development of various organs require support from cell division, consisting of quick connection of gene expression programs, acceleration of the translation programs, and quick regulation of protein synthesis ( Guo, 2018 ).…”
Section: Discussionsupporting
confidence: 88%
“…It is known that the expression of WNT11 is up-regulated during skin wound healing, indicating that the signal transduction of this gene may be active in the stage of wound healing and play an important role in the regeneration of hair follicles ( 43 ). BAMBI is an inhibitor of TGF-β family members and plays a role in hair follicle development ( 44 ). BAMBI is different in fetal skin, and the expression from 45 days to 135 days increases gradually in the embryonic stage, which is consistent with the development of hair follicles in the embryonic stage and can positively regulate the growth of hair follicles ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The GO term enrichment of “ribosome” and “structural constituent of ribosome”, and KEGG pathway enrichment of “ribosome” were observed in down-regulated genes. Several studies have identified a connection between the ribosome and hair growth [ 32 36 ]. Lv et al found that the ribosome pathway was the most significantly enriched pathway by skin transcriptome analysis and may be related to the development and the density of secondary wool follicles in Chinese Merino sheep [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified a connection between the ribosome and hair growth [ 32 36 ]. Lv et al found that the ribosome pathway was the most significantly enriched pathway by skin transcriptome analysis and may be related to the development and the density of secondary wool follicles in Chinese Merino sheep [ 32 ]. By miRNA sequencing and differentially expressed miRNAs analysis, the ribosome pathway may participate in dermal papilla cells viability and proliferation, and thereby affects hair cycling [ 34 ].…”
Section: Discussionmentioning
confidence: 99%